Substitusi rumput gajah dengan rumput laut coklat (Sargassum polycys-tum) terhadap produk metabolisme rumen dan kecernaan nutrien secara in vitro - Marselinus Hambakodu; Eko Pangestu; Joelal Achmadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
This research was conducted to assess the level of substitution of napier grass with brown seaweed (Sargassum polycystum) in diet of the goat on rumen metabolism product and nutrient digestibility in vitro. The experimental design used was completely randomized design with 4 treatments and 4 replications. Feed treatments consisted of T1 (control) = 50% napier grass + 50% concentrate; T2 = napier grass 37,5% + S. polycystum 12,5% + 50% concentrate; T3 = napier grass 25% + S. polycystum 25% + 50% concentrate; T4 = napier grass 12,5% + S. polycystum 37,5% + 50% concentrate. The result, substitution of napier grass with brown seaweed (S. polycystum) did not significant (P>0.05) effect on pH, N-NH3, VFA total, acetate, propionate, butyrate, adenosine triphosphate (ATP), dry matter digestibility, organic matter digestibility, and neutral detergent fiber digestibility. It is suggested that brown seaweed (S. polycystum) could replace napier grass on goat feed at up to 37,5%.